ANALISIS SEMIOTIK DAN LINGUISTIK STRUKTURAL PADA CERITA PENDEK "SEPATU USANG BUDI" KARYA DODI INDRA - Dewi Purwiyanti, Ratna; Septiana, Ika; Senowarsito (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This study analyzes in depth the sign system in the short story Sepatu Usang Budi by Dodi Indra through the semiotic study approach of Ferdinand de Saussure, with the main emphasis on the dichotomy of signifiers that are manifested in the physical form of the shoe such as damaged, shiny, or muddy conditions, as well as signifiers (signifiers).) which symbolizes abstract concepts such as existential struggle, social class identity, and a sense of alienation of the character. In addition, the analysis also highlights its arbitrary relationships that are not natural but depend on the conventions of language systems, thus forming differential structural meanings through narrative opposition. The method applied is descriptive qualitative with a focus on synchronic and diachronic text analysis as well as syntagmatic and paradigmatic in which the results of the study reveal that the shoe motif effectively reflects contemporary Indonesian socio-cultural issues such as the process of urbanization, economic inequality, and cultural identity conflict through a narrative opposition pattern (new versus damaged shoes that symbolize success versus failure), thus proving the relevance of Saussure's theory in the context Indonesian literature and makes a significant contribution to the enrichment of structural studies in the modern short story genre. The research data in the form of quotations, sign systems, and dialogues contained in five selected short stories from Dodi Indra were selected through purposive sampling techniques based on relevance to daily life Keywords: semiotics Ferdinand de Saussure, sign system, short story Shoes Obsolete Budi.